2015
DOI: 10.14746/rpeis.2015.77.3.22
|View full text |Cite
|
Sign up to set email alerts
|

Zaufanie do samorządu terytorialnego w Polsce – próba oceny

Abstract: Zaufanie do samorządu terytorialnego ma kluczowe znaczenie dla skuteczności podejmowanych przez jego jednostki działań w zakresie realizowania przypisanych zadań publicznych. W niniejszym artykule podjęto rozważania na temat zaufania do władzy, w tym do władzy samorządowej. Najważniejszy element opracowania stanowi jednak próba oceny poziomu zaufania do samorządu terytorialnego w Polsce. Pomiaru dokonano na trzy sposoby, analizując wyniki badań opinii publicznej, badając kształtowanie się frekwencji w wyborach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
2
0
1
Order By: Relevance
“…By their very nature, we just assign them normative precedence in political theory. The assumption of discrepancies between the state-centric and the local ideas of politics or power is well justified by the fact that in opinion polls, the level of trust in the self-government and central authorities when examined separately is highly divergent (Wiśniewski, 2015). Apart from the contemporary empirical data, we have at our disposal historical knowledge of local government models which variety may also be an argument for our assumption (Faliński, 2014).…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…By their very nature, we just assign them normative precedence in political theory. The assumption of discrepancies between the state-centric and the local ideas of politics or power is well justified by the fact that in opinion polls, the level of trust in the self-government and central authorities when examined separately is highly divergent (Wiśniewski, 2015). Apart from the contemporary empirical data, we have at our disposal historical knowledge of local government models which variety may also be an argument for our assumption (Faliński, 2014).…”
Section: Methodsmentioning
confidence: 97%
“…For example, the research conducted in most European countries on the problem of legitimacy of power showed that people distinguish between the legitimacy of central and local authorities (Lidstrom, Baldersheim, 2016). This is also evident in public opinion polls, where questions about trust in local authorities and central government give different results (Wiśniewski, 2015).…”
Section: The Problem Of Imaginariesmentioning
confidence: 97%
“…W coraz większym stopniu gminy będą odchodzić od bezpośredniego wykonywania zadań (świadczenia usług) na rzecz pełnienia funkcji zarządczej, polegającej na ukierunkowywaniu rozwoju danej jednostki terytorialnej, na co wiele lat temu zwracała uwagę Wojtasiewicz (2004). Ukierunkowanie tego rozwoju będzie się odbywać poprzez uchwalanie strategii rozwoju (być może także strategii rozwoju cyfrowego), kojarzenie podmiotów gospodarczych ze start-upami i ośrodkami badawczymi, zapraszanie do gmin (miast) operatorów nowych usług, np.…”
Section: Wybrane Aspekty Wpływu Nowych Technologii Na Gospodarkę Gminunclassified